In memory of cats : the camera and the ordinary moment : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Fine Arts at Massey University, Wellington, New Zealand - Korver, Ruth M. (Massey University, 2009)
In memory of cats: The camera and the ordinary moment looks at the way in which families use photographs to remember the past. Photography’s offer of memory is limited to a visual trace, so strategies of oral telling are examined to interrogate the way in which memories can be recovered from photographs. Martha Langford’s study of the similarities between structures in oral culture and the photograph album and Annette Kuhn’s strategies for reading family photographs in a broader historical context, are used to examine and recover memories from my own photographic archive. Using moving image to record those memories and then tell how that photographic evidence has shaped my present, is a process suggested by Linda Williams in her writing about how postmodern documentary can use the past to intervene in the present. Other documentary styles, performative documentary and the essay film, offer a structure for personal memories to be revisited and re-presented to public viewers. Offering a space for personal or specific memories to be understood or related to by a viewer is discussed by Lisa Saltzman, who looks at indexical forms other than the photograph, like casting and tracing. These ideas culminated in my video work, A Clowder of Cats, which explores the losses that have been a part of my history, through photographs of the cats my family has owned. The camera gives us a strategy to remember moments that may otherwise have been forgotten, and moving image provides a space for those ordinary moments to be bought back to the present.
Keywords: Personal memories; Photographs of cats; Video images; Friends and family; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410203 Photography studies